Increased Vascular Smooth Muscle Contractility in TRPC6(−)(/)(−) Mice - Dietrich, Alexander (American Society for Microbiology, 2005)
Among the TRPC subfamily of TRP (classical transient receptor potential) channels, TRPC3, -6, and -7 are gated by signal transduction pathways that activate C-type phospholipases as well as by direct exposure to diacylglycerols. Since TRPC6 is highly expressed in pulmonary and vascular smooth muscle cells, it represents a likely molecular candidate for receptor-operated cation entry. To define the physiological role of TRPC6, we have developed a TRPC6-deficient mouse model. These mice showed an elevated blood pressure and enhanced agonist-induced contractility of isolated aortic rings as well as cerebral arteries. Smooth muscle cells of TRPC6-deficient mice have higher basal cation entry, increased TRPC-carried cation currents, and more depolarized membrane potentials. This higher basal cation entry, however, was completely abolished by the expression of a TRPC3-specific small interference RNA in primary TRPC6(−)(/)(−) smooth muscle cells. Along these lines, the expression of TRPC3 in wild-type cells resulted in increased basal activity, while TRPC6 expression in TRPC6(−/−) smooth muscle cells reduced basal cation influx. These findings imply that constitutively active TRPC3-type channels, which are up-regulated in TRPC6-deficient smooth muscle cells, are not able to functionally replace TRPC6. Thus, TRPC6 has distinct nonredundant roles in the control of vascular smooth muscle tone.